2020
DOI: 10.1128/jvi.00403-20
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Inducible Gene I and Protein Kinase R, but Not Stress Granules, Mediate the Proinflammatory Response to Yellow Fever Virus

Abstract: Yellow fever virus (YFV) is an RNA virus primarily targeting the liver. Severe YF cases are responsible for hemorrhagic fever, plausibly precipitated by excessive pro-inflammatory cytokine response. Pathogen recognition receptors (PRRs), such as the cytoplasmic RIG-I-like receptors (RLRs), and the viral RNA sensor PKR are known to initiate a pro-inflammatory response upon recognition of viral genomes. Here, we sought to reveal the main determinants responsible for the acute cytokine expression occurring in hum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 66 publications
1
12
0
Order By: Relevance
“…We further investigated the importance of type I IFN signaling in the restriction SARS-CoV-2 growth by profiling transcriptional responses in human liver carcinoma cell lines, Huh7 and Huh7.5, at 0 and 48 HPI (Figure 3). Previous studies with hepatitis C, dengue, and yellow fever viruses have shown that enhanced viral permissivity in Huh7.5 cells compared with Huh7 cells is due to defective RIG-1-mediated signaling (both cell lines lack IFNA10 and TRIM56) (Beauclair et al, 2020;Chatel-Chaix et al, 2016;Chen et al, 2021;Sumpter et al, 2005). In line with these previous studies, Huh7.5 cells supported greater viral growth and release compared with Huh7 cells (Figures 1A-1C).…”
Section: Infection Of Huh75 Cells Versus Huh7 Cells Leads To More Div...supporting
confidence: 86%
“…We further investigated the importance of type I IFN signaling in the restriction SARS-CoV-2 growth by profiling transcriptional responses in human liver carcinoma cell lines, Huh7 and Huh7.5, at 0 and 48 HPI (Figure 3). Previous studies with hepatitis C, dengue, and yellow fever viruses have shown that enhanced viral permissivity in Huh7.5 cells compared with Huh7 cells is due to defective RIG-1-mediated signaling (both cell lines lack IFNA10 and TRIM56) (Beauclair et al, 2020;Chatel-Chaix et al, 2016;Chen et al, 2021;Sumpter et al, 2005). In line with these previous studies, Huh7.5 cells supported greater viral growth and release compared with Huh7 cells (Figures 1A-1C).…”
Section: Infection Of Huh75 Cells Versus Huh7 Cells Leads To More Div...supporting
confidence: 86%
“…These results support a model where SGs act as a platform for recognition of viral RNAs and activation of innate immune signaling. Other studies, however, observed that disruption of SGs (by drug treatments, mutating eIF2α, or depleting PKR or SG components) did not reduce interferon production [51–53]. Therefore, a growing body of evidence implicates SGs in innate immune signaling, but their role might be restricted to specific viruses and conditions, depending on the properties and localization pattern of the viral genome [23].…”
Section: Role Of Sgs In Antiviral Innate Immunitymentioning
confidence: 99%
“…Both RIG-I and MDA5 are involved in responses to dengue virus serotype-2 (DENV-2) infection in mouse embryonic fibroblasts [ 36 ] and Zika virus infection in human trophoblasts [ 37 ]. Concerning the role of RLRs in YFV infection, it was reported that replication of YFV vaccine strain YF-17D in human pDCs and pDC-like cell lines, and YFV reference strain Asibi in human hepatoma cells stimulated type I IFN production through activation of RIG-I [ 38 , 39 ].…”
Section: Resultsmentioning
confidence: 99%